Development of magnetic imaging system using giant magnetoresistive (GMR) sensor - Misron, Norhisam; Roslan, Muhammad Kamel; Aris, Ishak; Hamidon, Mohd Nizar; Tashiro, Kunihisa (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Research in non-destructive evaluation is constantly increasing the sensitivity of detection of small cracks embedded deep in layered wall structures. This paper presents the early development stage of magnetic imaging system based on Giant Magneto-resistance (GMR) sensors. The system is a simple and capable of ferromagnetic shapes detection based on the Magnetic Flux Leakage Testing principle. The sensing elements made up of an array of GMR sensors to detect induced magnetic field on a ferromagnetic shapes under evaluation. The whole system consists of GMR sensors as the sensing element, DAQ card for data collection, LABView software for the image processing and induction coil as sourced of magnetic field. Data produced from the GMR sensors is collected and transferred to the Data Aqcuisition (DAQ) Card which finally will be manually processed in LABView programming software. The experimental results illustrated the magnetic image of specimens’ steel of various shape e.g square, round and triangle. The results proved the capability of the system to perform shape evaluation on ferromagnetic materials.